2022
DOI: 10.1038/s41574-022-00734-y
|View full text |Cite
|
Sign up to set email alerts
|

A global view of hypertensive disorders and diabetes mellitus during pregnancy

Abstract: Two important maternal cardiometabolic disorders (CMDs), hypertensive disorders in pregnancy (HDP) (including pre-eclampsia) and gestational diabetes mellitus (GDM), result in a large disease burden for pregnant individuals worldwide. A global consensus has not been reached about the diagnostic criteria for HDP and GDM, making it challenging to assess differences in their disease burden between countries and areas. However, both diseases show an unevenly distributed disease burden for regions with a low income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 263 publications
1
53
2
Order By: Relevance
“…In 2020, Gemechu et al reported a prevalence of 0.9% (95% CI: 0.4–1.8) for only gestational hypertension in a systematic review and meta-analysis of 70 studies [ 4 ]. The prevalence found in our study is relatively high compared to the prevalence of 0.3% for women of childbearing age reported by Jiang et al in 2022 [ 12 ]. However, large differences have been reported in the prevalence of HBP [ 8 , 20 , 20 , 22 – 24 ].…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In 2020, Gemechu et al reported a prevalence of 0.9% (95% CI: 0.4–1.8) for only gestational hypertension in a systematic review and meta-analysis of 70 studies [ 4 ]. The prevalence found in our study is relatively high compared to the prevalence of 0.3% for women of childbearing age reported by Jiang et al in 2022 [ 12 ]. However, large differences have been reported in the prevalence of HBP [ 8 , 20 , 20 , 22 – 24 ].…”
Section: Discussioncontrasting
confidence: 66%
“…Maternal age, household income, occupation, parity, and residential area were not associated with HBP during pregnancy in our study. Several studies have reported an association between sociodemographic characteristics [ 12 , 20 , 25 ]. This difference may be explained by the lack of statistical power because we conducted this study to identify the prevalence of HBP during pregnancy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual-level polygenic scores were generated in the tuning and test datasets as the sum of genotypes*weights using PLINK. We used logistic regression to test the association of each PRS with preeclampsia/eclampsia and gestational hypertension with adjustment for age, age 2 , and PC 1-10. PRS were tuned in the UK Biobank.…”
Section: Gene Expression In Human Aortic Tissuementioning
confidence: 99%
“…It complicates up to 10% of pregnancies [5,6] and presents with a combination of different signs and symptoms such as hypertension, proteinuria, biochemical abnormalities, headaches, edema and/or abdominal pain [5]. If left untreated, it can rapidly progress to multiorgan failure, seizures, stroke and death (in the mother) and intrauterine growth restriction, neurological injuries, for example cerebral palsy and death (in the baby) [5,7 ▪ ,8]. These patients and their offspring are also at increased risk of cardiometabolic disorders later in life [4 ▪ ,5,8]…”
Section: Introductionmentioning
confidence: 99%